The efficacy of CRISPR-mediated cytosine base editing with the RPS5a promoter in Arabidopsis thaliana - Minkyung Choi (Nature Portfolio, 2021)
Abstract CRISPR/Cas9-mediated genome editing is an important and versatile technology in modern biological research. Recent advancements include base-editing CRISPR tools that enable targeted nucleotide substitutions using a fusion protein comprising a nickase variant of Cas9 and a base deaminase. Improvements in base editing efficiencies and inheritable of edited loci need to be made to make CRISPR a viable system in plants. Here, we report efficiency of cytosine base editors (CBEs) in Arabidopsis thaliana by applying the strong endogenous RPS5a promoter to drive the expression of nickase Cas9 and either rAPOBEC1 from rat (BE3) or the PmCDA1 activation-induced cytidine deaminase from sea lamprey (AIDv2). Compared with the strong heterologous CaMV35S promoter of viral origin, the RPS5a promoter improved CBE efficiency by 32% points with the number of T1 plants showing over 50% conversion ratio when the LFY gene was targeted. CBE induced nonsense mutations in LFY via C-to-T conversion, which resulted in loss-of-function lfy phenotypes; defects in LFY function were associated with the targeted base substitutions. Our data suggest that optimal promoter choice for CBE expression may affect base-editing efficiencies in plants. The results provide a strategy to optimize low-efficiency base editors and demonstrate their applicability for functional assays and trait development in crop research.